Antisolvent Crystallization of Polymorphs of L‐Histidine. Issue 6 (18th April 2018) - Punmalee, Neeranuch; Wantha, Lek; Flood, Adrian E.
Abstract: Antisolvent crystallization is the most common method to study solvent effects on polymorphic crystallization. L ‐Histidine ( L ‐his) served as a model substance. Acetonitrile, acetone, and methanol were selected as antisolvents, with water as solvent. The formation of L ‐his polymorphs in antisolvent crystallization as a function of supersaturation, antisolvent volume fraction, and temperature was studied. The solubility of polymorph A of L ‐his decreased with increasing volume fraction of antisolvent and increased with higher temperature. The metastable polymorph B of L ‐his was obtained at higher antisolvent volume fraction and supersaturation. At lower antisolvent volume fraction and supersaturation, a mixture of polymorphs A and B was detected. Abstract : Antisolvent crystallization is the most popular method to evaluate solvent effects on polymorphic crystallization. Polymorphs of L ‐histidine were crystallized with acetonitrile, acetone, and methanol as antisolvents. The metastable polymorph B of L ‐histidine was obtained at higher antisolvent volume fraction and supersaturation while at lower values a mixture of polymorphs A and B was achieved.